1H NMR-Based Metabolomics and Lipid Analyses Revealed the Effect of Dietary Replacement of Microbial Extracts or Mussel Meal with Fish Meal to Arctic Charr (Salvelinus alpinus) - Liane Wagner; Pedro Gómez-Requeni; Ali A. Moazzami; Torbjörn Lundh; Aleksandar Vidakovic; Markus Langeland; Anders Kiessling; Jana Pickova (Fishes, 2019)
The effects of replacing 40% of dietary fish meal (FM) in a reference diet (REF) with either mussel meal (MM), zygomycete fungi (ZYG), extracted baker’s yeast (EY), or non-extracted baker’s yeast (NY) on the lipid and metabolic profile of Arctic charr (Salvelinus alpinus) were investigated. After a 14-week feeding trial, liver and muscle tissues were collected for lipid (lipid content, lipid class, fatty acid composition) and 1H NMR-based metabolomics analyses (aqueous and chloroform phases). Lipid analyses showed that fish fed ZYG diet had lower liver lipid content and thereby 10% higher level of docosahexaenoic acid compared with REF. Metabolomics analyses showed that on the one hand fish fed NY diet affected liver metabolites (2–3 fold higher concentrations of e.g., n,n-dimethylglycine and betaine) compared with REF, while, on the other hand, the muscle metabolic fingerprint was mainly affected by EY. In general, affected metabolites (e.g., alanine, anserine, betaine, hydroxyproline, isoleucine, malonate, n,n-dimethylglycine, proline, succinate, and valine) in fish fed test diets suggested that the test meal ingredients caused mainly a response in muscle metabolism. Fish metabolism was least affected by MM, which suggests that it may be suitable to replace fish meal in Arctic charr diets.